El principio de libertad probatoria y su incidencia en las sentencias emitidas por el Tribunal de Garantías Penales de la Unidad Judicial Penal con sede en el cantón Riobamba, en el período de enero a diciembre del año 2015. - Vidal Lazo, Edgar Xavier (2017)
This research work determines how the principle of probationary freedom affects in the judgments issued by the Court of Criminal Guarantees of the Criminal Judicial Unit, in Riobamba, from January to December during the year 2015; for this, a doctrinal, legal and critical analysis of the application of the principle of probationary freedom is carried out, and how it influences in the Justice Administrators. Chapter I contains the Reference Framework, which is about the approach and problema formulation of this investigation; the general and specific goals that were achieved, as well as the justification and importance of the problema. Chapter 2 contains the Theoretical Framework, in which the unit I is developed, which refers to the topics and sub-themes on the constitutional and legal principles applicable to the trial in the trial audiences of the Criminal Court. Chapter 3 refers to the Methodological Framework which explains how the research was carried out; it describes the processes, methods, techniques and instruments used in the performance of the work. It also manifests the population involved, as well as the analysis and interpretation of results; Unit 2 contains themes and sub-themes on the analysis of the principle of probationary freedom; Unit 3 contains the topics and sub-themes on the assessment of the evidence in the judgments issued by the Criminal Court; Unit 4 is about the international instruments applied in criminal matters, analysis of a case study, and analysis of jurisprudence; and finally, Unit 5 has to do with the hypothetical unit, operationalization of variables, and definition of basic terms. Chapter 4 establishes the conclusions and recommendations that have been reached, after having carried out the investigation work; it also contains the reference material used for the development of the theoretical framework and finally the annexes of this investigation.